Glutaric Aciduria Type I Missed by Newborn Screening: Report of Four Cases from Three Families - Johannes Spenger; Esther M. Maier; Katharina Wechselberger; Florian Bauder; Melanie Kocher; Wolfgang Sperl; Martin Preisel; Katharina A. Schiergens; Vassiliki Konstantopoulou; Wulf Röschinger; Johannes Häberle; Thomas Schmitt-Mechelke; et al. (MDPI AG, 2021)
Glutaric aciduria type I (GA-1) is a rare autosomal-recessive disorder of the degradation of the amino acids lysine and tryptophan caused by mutations of the GCDH gene encoding glutaryl-CoA-dehydrogenase. Newborn screening (NBS) for this condition is based on elevated levels of glutarylcarnitine (C5DC) in dried blood spots (DBS). Here we report four cases from three families in whom a correctly performed NBS did not detect the condition. Glutarylcarnitine concentrations were either normal (slightly below) or slightly above the cut-off. Ratios to other acylcarnitines were also not persistently elevated. Therefore, three cases were defined as screen negative, and one case was defined as normal, after a normal control DBS sample. One patient was diagnosed after an acute encephalopathic crisis, and the other three patients had an insidious onset of the disease. GA-1 was genetically confirmed in all cases. Despite extensive efforts to increase sensitivity and specificity of NBS for GA-1, by adjusting cut-offs and introducing various ratios, the biological diversity still leads to false-negative NBS results for GA-1.